2008
DOI: 10.4103/0974-1208.44113
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovaries and infertility: Our experience

Abstract: BACKGROUND:Polycystic ovary syndrome (PCOS) is one of the most common (15–20%) endocrine disorders in women of childbearing age. Although it is a major cause of infertility, its etiology remains unknown and its treatment difficult.AIM:To evaluate the incidence, treatment and outcome of patients with PCOS.DESIGN:Retrospective analysis.MATERIALS AND METHODS:PCOS patients (914 of the 1057) attending the outpatient department (OPD) from June 2003 to February 2008 were evaluated for this study. Of the 914 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…Polycystic ovary syndrome (PCOS) is a multifactiorial and polygenic pathology that manifests itself with a wide spectrum of signs and symptoms that are related to the disturbances of reproductive, endocrine, and metabolic functions at various degrees resulting in a heterogenous presentation of the disease [1]. The diagnostic criteria for (PCOS) has undergone several changes in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a multifactiorial and polygenic pathology that manifests itself with a wide spectrum of signs and symptoms that are related to the disturbances of reproductive, endocrine, and metabolic functions at various degrees resulting in a heterogenous presentation of the disease [1]. The diagnostic criteria for (PCOS) has undergone several changes in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, many studies underscore that treatments for assisted conception, and particularly IVF, which is the most studied of these, are a source of stress for the couple who make a great emotional investment in these treatmentssadness, depression, anxiety hopelessness, and anger are common in infertile couples underwent IVF treatment. The emotional distress is particularly great when waiting for treatment outcome, in the case of unsuccessful treatment and in the cycles following the first attempt it also depends on the ability of the couple to cope with this condition [10][11][12][13][14][15][16] .…”
Section: Variablesmentioning
confidence: 99%
“…[9] Polycystic ovary syndrome is one of the most common (15-20%) endocrine disorders in women of childbearing age .It was found that of the 2270 infertility patients attending infertility clinic , 46.50% (1057) had PCOS. [10] 1.2 Objectives Of The Study  To assess the prevalence of Poly Cystic Ovarian Syndrome among women attending Gyne OPD of selected hospital.  To assess the knowledge and practice of women with PCOS regarding Poly Cystic Ovarian Syndrome  To develop a Health Care Package on PCOS and its management.…”
Section: Introductionmentioning
confidence: 99%